Consumer desire for control as a barrier to new product adoption - Faraji‐Rad, Ali; Melumad, Shiri; Johar, Gita Venkataramani (Journal of Consumer Psychology, 2017)
AbstractThis research examines the relationship between desire for control and acceptance of new products. We hypothesize that desire for control—the need to personally control outcomes in one's life—acts as a barrier to new product acceptance. Three experiments provide support for this hypothesis. This effect holds when desire for control is high as a dispositional trait (Studies 1 and 3) and when it is situationally induced (Study 2). We also identify an intervention to increase new product acceptance based on the idea that new products threaten one's sense of control. Specifically, framing new products as potentially enhancing one's sense of control increases acceptance of new products by those high in desire for control (Study 3). This finding offers some evidence for the underlying process and helps guide managerial actions.